2021
DOI: 10.1073/pnas.2024015118
|View full text |Cite
|
Sign up to set email alerts
|

Structure of Arabidopsis CESA3 catalytic domain with its substrate UDP-glucose provides insight into the mechanism of cellulose synthesis

Abstract: Cellulose is synthesized by cellulose synthases (CESAs) from the glycosyltransferase GT-2 family. In plants, the CESAs form a six-lobed rosette-shaped CESA complex (CSC). Here we report crystal structures of the catalytic domain of Arabidopsis thaliana CESA3 (AtCESA3CatD) in both apo and uridine diphosphate (UDP)-glucose (UDP-Glc)–bound forms. AtCESA3CatD has an overall GT-A fold core domain sandwiched between a plant-conserved region (P-CR) and a class-specific region (C-SR). By superimposing the structure of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 48 publications
0
25
4
Order By: Relevance
“…A recent crystal structure of the catalytic domain of the primary cell wall AtCESA3 revealed that the catalytic core is capable of forming a homodimer at an interface involving β-strand 6 (β6) and a-helix 9 (a9) and that homodimerization may play a role in preventing premature CSC assembly (Qiao et al, 2021). A similar mechanism was proposed in an earlier study of secondary cell wall CSC assembly (Atanassov et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent crystal structure of the catalytic domain of the primary cell wall AtCESA3 revealed that the catalytic core is capable of forming a homodimer at an interface involving β-strand 6 (β6) and a-helix 9 (a9) and that homodimerization may play a role in preventing premature CSC assembly (Qiao et al, 2021). A similar mechanism was proposed in an earlier study of secondary cell wall CSC assembly (Atanassov et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…The DDG, DXD, TED and QXXRW motifs in the catalytic domain are conserved among plant and bacteria and they participate in donor and acceptor UDP-glucose binding, glucan chain polymerization and elongation (Morgan et al, 2013; Morgan et al, 2016; Purushotham et al, 2020). A recent crystal structure of the AtCESA3 catalytic domain reveals the ability to form homodimers through contacts between β-strand 6 (β6) and α-helix 9 (a9) of adjacent subunits and bimolecular fluorescence complementation confirms that homodimers form in the Golgi apparatus (Qiao et al, 2021). This could represent a catalytically-inactive structure of CESA subunits and perhaps is an important form of regulation for CSC assembly, as proposed previously (Atanassov et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the homotrimer of cotton CesA7 was stabilized by the transmembrane helix 7 (TM7) and the PCR domains, whereas the CSR is located at the periphery of the catalytic domain, suggesting an involvement in the interaction with other rosette units or non-CesA auxiliary proteins [ 48 ]. Additionally, the crystal structure of Arabidopsis CesA3 catalytic domain with its substrate UDP-glucose provided new insights into the mechanism of cellulose synthesis [ 49 ]. This work revealed the structural basis of how the substrate UDP-Glucose and a metal ion Mn 2+ which is required for cellulose synthesis, are coordinated in plant CesA complexes.…”
Section: The Architecture Of Cesa Catalytic Domainmentioning
confidence: 99%
“…In agreement with previous reports, the crystal structure of Arabidopsis CesA3 catalytic domain was divided into the core domain, the PCR and the CSR domain. The core catalytic domain, including the catalytic sites, was composed of a β -sheet with eight strands, flanked by two α -helices on one side and two α -helices with three β -strands on the other side [ 49 ]. An insertion of a cellulose binding helix towards the catalytic region was proposed without forming a strong interaction with the rest of the catalytic domain, proposing that it is flexible in the absence of cellulose and transmembrane helices [ 49 ].…”
Section: The Architecture Of Cesa Catalytic Domainmentioning
confidence: 99%
See 1 more Smart Citation